Comparison of clinical and procedural outcomes between high‐power short‐duration, standard‐power standard‐duration, and temperature‐controlled noncontact force guided ablation for atrial fibrillation. (19th January 2021) - Dikdan, Sean J.; Junarta, Joey; Bodempudi, Sairamya; Upadhyay, Naman; Pang, Zachary; Frisch, Daniel R.
Abstract: Introduction: High‐power short‐duration (HPSD) ablation is a novel strategy using contact force‐sensing catheters optimized for power‐controlled radiofrequency ablation for atrial fibrillation (AF). This study investigates the outcomes of HPSD (50 W delivered for up to 15 s, Lesion Size Index of 5–6) compared to standard‐power standard‐duration (SPSD) (20–25 W until 400–500 gram seconds, up to 60 s) and temperature‐controlled noncontact (TCNC) (20‐40 W up to 60 s of ablation) settings. Methods: We studied consecutive cases of patients with AF undergoing pulmonary vein isolation with TCNC, SPSD, and HPSD between January 7th, 2013 and January 11th, 2019. Procedural data collected include time to isolate the left (LPVT) and right pulmonary veins (RPVT), total ablation time (TAT), and radiofrequency ablation delivery time (RADT). Clinical data collected include sinus rhythm maintenance postprocedure. Results: One hundred and seventy‐one patients were studied (44 TCNC, 51 SPSD, 76 HPSD). RADT was shorter when comparing HPSD to SPSD (25 vs. 41 min; p  < .01), HPSD to TCNC (25 vs. 76 min; p  < .01), and SPSD to TCNC groups (41 vs. 76 min; p  < .01). TAT, LPVT, and RPVT were reduced between HPSD versus SPSD, HPSD versus TCNC, and SPSD versus TCNC groups, respectively ( p  < .01). There was no difference in sinus rhythm maintenance by Kaplan–Meier survival analysis (log rank test p  = .12), after 3 or 12 months between groups overall, and when stratified by AF type, left atrial volume, CHA2 DS2 ‐VASc score, or left ventricular ejection fraction. Conclusion: AF ablation with HPSD reduced procedure times with similar sinus rhythm maintenance compared to SPSD and TCNC.